Chromosomal distribution of interstitial telomeric sequences as signs of evolution through chromosome fusion in six species of the giant water bugs (Hemiptera, Belostoma) - Chirino, Monica Gabriela (2017)
Tandem arrays of TTAGG repeats show a highly conserved location at the telomeres across the phylogenetic tree of arthropods. In giant water bugs Belostoma, the chromosome number changed during speciation by fragmentation of the single ancestral X chromosome, resulting in a multiple sex chromosome system. Several autosome–autosome fusions and a fusion between the sex chromosome pair and an autosome pair resulted in the reduced number in several species. We mapped the distribution of telomeric sequences and interstitial telomeric sequences (ITSs) in Belostoma candidulum (2n = 12 + XY/XX; male/female), B. dentatum (2n = 26 + X1X2Y/X1X1X2X2), B. elegans (2n = 26 + X1X2Y/X1X1X2X2), B. elongatum (2n = 26 + X1X2Y/X1X1X2X2), B. micantulum (2n = 14 + XY/XX), and B. oxyurum (2n = 6 + XY/XX) by FISH with the (TTAGG)n probes. Hybridization signals confirmed the presence of TTAGG repeats in the telomeres of all species examined. The three species with reduced chromosome numbers showed additional hybridization signals in interstitial positions, indicating the occurrence of ITS. From the comparison of all species here analyzed, we observed inverse relationships between chromosome number and chromosome size, and between presence/absence of ITS and chromosome number. The ITS distribution between these closely related species supports the hypothesis that several telomere–telomere fusions of the chromosomes from an ancestral diploid chromosome number 2n = 26 + XY/XX played a major role in the karyotype evolution of Belostoma. Consequently, our study provide valuable features that can be used to understand the karyotype evolution, may contribute to a better understanding of taxonomic relationships, and also elucidate the high plasticity of nuclear genomes at the chromosomal level during the speciation processes.